Livro raro: dispositivo interdisciplinar: seu conteúdo e sua preservação - Ribeiro, Candido Marcilio (2018)
John Milton wrote: For books are not merely inanimate objects, but contain in themselves a potential life, which is as active as that which animates the creature of whom they are the progeny; and not only that, but they still preserve, as if in a flask, the purest efficiency extracted from that living intellect that begot them. (BARTILETT, 2013, p. 23) The life of a book is its expression of communication to the general public. The book, according to the text of John Milton, ceases to be an inanimate object because its content touches the life of everyone who bends over it. Our work envisages a content from a BOOK / JOURNAL dated from 1927, the contents of which relate to the Bicentennial of coffee activity in Brazil. This work is enriched with economic, cultural, social and engravings ora paintings, sometimes well-tailored photographs with appropriate illustration. However, given the time and the peculiar material of said work; it should be noted a reasonable wear, for even amid the preservation of the Historic Center of the Mackenzie Presbyterian University what can be expected is an expected wear and tear is acceptable. We presume, that somehow we ask to suggest intervention as to the restoration and preservation of this brilliant and rare work.